Subcutaneous Tocilizumab Versus Placebo in Combination With Disease‐Modifying Antirheumatic Drugs in Patients With Rheumatoid Arthritis1. Issue 11 (November 2014) - Kivitz, Alan; Olech, Ewa; Borofsky, Michael; Zazueta, Beatriz M.; Navarro‐Sarabia, Federico; Radominski, Sebastião C.; Merrill, Joan T.; Rowell, Lucy; Nasmyth‐Miller, Clare; Bao, Min; Wright, Stephen; Pope, Janet E.
<x xml:space="preserve">Abstract</x> Objective The efficacy and safety of subcutaneous tocilizumab (TCZ‐SC) versus subcutaneous placebo (PBO‐SC) was evaluated in patients with rheumatoid arthritis who had an inadequate response to disease‐modifying antirheumatic drugs in the BREVACTA study. Methods Patients (n = 656) were randomized 2:1 to receive TCZ‐SC 162 mg every other week or PBO‐SC every other week for 24 weeks; 20% previously received anti–tumor necrosis factor treatment. Escape therapy with TCZ‐SC 162 mg weekly was offered from week 12 for inadequate response. The primary end point was the American College of Rheumatology 20% improvement (ACR20) response at week 24. The key secondary outcomes were radiographic progression and safety. Results TCZ‐SC was superior to PBO‐SC for ACR20 response at week 24 (60.9% versus 31.5%; P < 0.0001). All secondary end points showed TCZ‐SC to be superior to PBO‐SC, including ACR50 and ACR70 response (40% and 20% for TCZ‐SC, respectively, and 12% and 5% for PBO‐SC, respectively; P < 0.0001 for both) and Disease Activity Score in 28 joints (DAS28) remission (DAS28 <2.6; 32% versus 4% [P < 0.0001]). The mean change in modified Sharp/van der Heijde score was significantly lower in the TCZ‐SC group than the PBO‐SC group (0.62 versus 1.23; P = 0.0149). Adverse events (AEs) and serious AEs (SAEs) were comparable between the TCZ‐SC and PBO‐SC groups; 4.6% and 3.7% of patients had at least 1 SAE, respectively, and infection was the most common SAE in 2.1% and 1.8% of patients, respectively. More injection site reactions occurred with TCZ‐SC than PBO‐SC (7.1% versus 4.1%). No anaphylaxis or serious hypersensitivity reactions occurred. There were 3 deaths in the TCZ‐SC group and 0 in the PBO‐SC group. Conclusion TCZ‐SC every other week had significantly greater efficacy, including ACR end points and inhibition of joint damage, compared with PBO‐SC. TCZ‐SC was well tolerated and its safety profile was comparable with that of previous intravenous TCZ studies.